Drag regimes of circular discs at different inclinations. (15th December 2022) - Satheesh, Sukruth; Spohn, Andreas; Kerhervé, Franck; Cordier, Laurent
Abstract: Experiments on circular and square plate models were performed in a low-speed water tunnel at a fixed Reynolds number [ O ( 10 4 ) ] for inclinations between 0° and 90° with respect to the flow direction. The experiments focus on drag force evolution and the associated flow structures to predict the drag regimes across the range of inclinations considered. Measurements show that drag increases rapidly with inclination for small angles, while at high angles it being nearly independent of inclination. The change between these drag regimes takes place at an inclination of 54°, with hydrogen bubble and PIV flow visualizations indicating this to be accompanied by a change in the wake flow structure as well. Trailing vortices at low angles suggests the existence of induced drag, while shedding of shear layers from all around model circumference at high angles points to the dominance of pressure drag as in the case of bluff bodies. Highlights: Limits for bluff body definition identified through drag force measurements. Drag coefficient saturates at 60°, later almost inclination independent. Critical angle demarcates the pressure drag and induced drag dominated regimes. Critical angle of 54° identified through experiments and empirical formula. PIV shows reorganization of shear layers to be source for observed drag trend.